Gender Differences in Self-concept among Adolescent Students of Uttarakhand - Rai, Dr Geeta (INDIAN EDUCATIONAL REVIEW, 2012)
The purpose of this study was to determine gender differences, region of residence and type of management on the self-concept of adolescents. A random sampling method was followed. The sample consisted of 800 respondents studying in secondary and higher secondary schools of Uttarakhand. The data was collected personally through a questionnaire on self-concept developed by R.K. Saraswat. It consisted of 6 dimensions of self-concept. Results indicated that boys and girls did not differ on total self-concept. However, significant differences were found between the groups formed on the basis of region of residence and type of management with respect to their overall self-concept at 0.05 level of significance.